Development of Measuring Device for Non-Invasive Blood Sugar Levels Using Photodiode Sensor - Dwi S, Frendi Agung; Utomo, Bedjo; Sumber, Sumber (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
Diabetes mellitus is one of the deadliest diseases faced by Indonesians. To measure blood sugar levels, the most widely used tool is an invasive tool, namely by injuring the patient's body. Techniques like this make people reluctant to measure glucose levels in their blood regularly. Therefore, this research aims to design and build a non-invasive blood sugar measuring device using a photodiode sensor. So that this tool can be used by all groups, both medical and non-medical personnel to measure blood sugar non-invasively. In this study, blood was drawn from several patients with Miletus diabetes and carried out direct blood measurements using a photodiode sensor. The results obtained from this study are that there is an error value in the voltage measurement circuit with the calculation of the resistance value to obtain the voltage value. The error value obtained is 5%, the linear regression value is 0.996. From the measurement results, it can be concluded that the photodiode sensor can be used to measure blood sugar non-invasively